Public procurement trajectories in Tanzania: a review of reforms, practices, and compliance - Alban D. Mchopa; Ismail Abdi Changalima; Gabriel R. Sulle; Rahim M. Msofe (Cogent Business & Management, 2024)
Over decades, public procurement in Tanzania experienced critical reforms; however, not much is known about the reforms and hence there is a dearth of comprehensive reviews about them. The current study reviews existing literature relating to public procurement reforms, practices, and compliance in Tanzania. By employing a systematic literature review, the study draws upon 65 publications from Scopus and Google Scholar databases. Findings unveil that the implementation of public procurement laws and regulations has significantly improved transparency, accountability, and fairness in public procurement undertakings. The foundation for a well-organized institutional framework that emphasizes decentralization, standardization, and governance over public procurement has also been established by these reforms. Despite these positive contributions, certain reforms have introduced challenges due to interference and uncoordinated efforts that hamper public procurement activities. The study exclusively focuses on journal articles from Scopus and Google Scholar, excluding other publication forms like book reviews and conference proceedings. While acknowledging this limitation, the article serves as the pioneering systematic review profiling public procurement reforms in Tanzania, shedding light on professional dilemmas and compliance issues. Given the limited literature on the subject, this study enriches the existing knowledge and offers valuable insights for scholars, procurement practitioners, public entities, and stakeholders.
Keywords: 650; Public procurement; reforms; governance; compliance; professionalism; Tanzania